1967
DOI: 10.1002/recl.19670860904
|View full text |Cite
|
Sign up to set email alerts
|

Activity coefficients of individual ions

Abstract: Existing methods for the estimation of the primary medium effect for individual ions are critically reviewed and an improved method for its estimation is developed.By this method the primary medium effect of the hydrogen ion has been determined for the transfer from water to methanol-water mixtures and methanol. The medium elfect of the alkali and the halide ions are then also known.The accuracy of the values so obtained for the individual ions is of the same order as the accuracy of experimentally determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1974
1974
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…To overcome the LJP problems, we recently suggested a procedure to determine Gibbs transfer energies of single ions Δ tr G°(i, S 1 !S 2 ) without extra-thermodynamic assumptions. [30] This procedure contains a sub-step that aims to determine each part C of both LJPs in cell II (see below) using a method proposed by Alfenaar, et al [31] However, our reassessment of Equation (7) showed that this step cannot be performed with the proposed method in the special case of ionic liquids (for details, see the Supporting Information). By contrast, experimental evidence for the cancellation of parts A and the ineffectiveness of parts B for S 2 being water and S 1 being acetonitrile (AN) were demonstrated.…”
Section: Methodsmentioning
confidence: 99%
“…To overcome the LJP problems, we recently suggested a procedure to determine Gibbs transfer energies of single ions Δ tr G°(i, S 1 !S 2 ) without extra-thermodynamic assumptions. [30] This procedure contains a sub-step that aims to determine each part C of both LJPs in cell II (see below) using a method proposed by Alfenaar, et al [31] However, our reassessment of Equation (7) showed that this step cannot be performed with the proposed method in the special case of ionic liquids (for details, see the Supporting Information). By contrast, experimental evidence for the cancellation of parts A and the ineffectiveness of parts B for S 2 being water and S 1 being acetonitrile (AN) were demonstrated.…”
Section: Methodsmentioning
confidence: 99%
“…Step c), Determination of part C of the LJPs: This operation only becomes relevant, if parts A and B of LJP1 and LJP2 of cell I can be disregarded and only C1 and C2 are operative. The procedure is adopted from Alfenaar et al . and the determination of part C between the solvent S and the IL needs two further values which can be determined straightforwardly: the transference number of M + ( t M+ ) in S and IL and the Gibbs energy of transfer of the salt MZ from S to IL .…”
Section: Figurementioning
confidence: 99%
“…Reasoning: Generally, Equation (7) describes the origin of the LJP as changes of the chemical potentials μ i of all particles i during the transfer over the S 1 S 2 junction ( t i r is the reduced transference number of i). This term is usually split into terms concerning charged species and uncharged species trueEj=-1FS1S2itirdμi …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The value of 6G for the individual ions tr were taken as the value of 6G at infinite counter ion radius (i.e., tr -1 r = 0). Alfenaar and de Ligny (1967) used a similar extrapolation method but included a neutral component, based on the solub ilities of the appropriate inert gas, in their values of 6G . tr…”
Section: Chapter Imentioning
confidence: 99%